하치조신경 마취 후 전기치수검사기(Electric pulp tester)를 이용한 하순부 감각 변화 평가 - 구명숙(Myong-Suk Ku); 김진욱(Jin Wook Kim); 전영훈(Young Hoon Jeon); 권대근(Tae Geon Kwon); 이상한(Sang Han Lee) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2011)
Introduction: As dental implant surgery is becoming increasingly popular, it has become one of the causes for the hypesthesia of the inferior alveolar nerve, along with other surgical procedures, such as a third molar extraction. In addition, it tends to cause legal problems between the operator and patient. Therefore, there must be a proper method that is reliable, objective and economical to assess the nerve impairment. For this reason, an attempt was made to use an Electric Pulp Tester to assess inferior alveolar nerve block anesthesia. Materials and Methods: Thirty patients were tested. Electric pulp testing of the lower jaw skin was performed at the three different times, before anesthesia, at the onset of sensory changes and after 15 minutes waiting from the onset, and on the 10 points of the chin, which produced 10 sections on the skin area. Results: Twenty seven patients (90%) could feel the electric stimulus on the chin at all 10 points before local anesthesia and the scores represent the statistical differences between the right and left points except R4 and L4. After anesthesia, the difference between the right and left points (L3-R3,L4-R4, L5-R5) increased significantly with time but two points (L2, R2) showed no significant difference. The scores on the left chin (L3, L4, L5)increased, whereas the other points (R1-R5, L1, L2) showed no significant differences. Conclusion: This study highlights the potential clinical use of an electric pulp tester for an assessment of inferior alveolar nerve impairment. KCI Citation Count: 0